Avascular Osteonecrosis in Systemic Sclerosis Patient: Risk Factors and Role ofVasculopathy? - Safarina Kharima Laitupa (Indonesian Rheumatology Associantion, 2021)
Avascular Necrosis (AVN) or osteonecrosis refers to the death of osteocytes andosteoblasts. Sites such as the femoral head, the head of the humerus and themandibular with restricted access to local blood supply are particularly vulnerableto osteonecrosis. Various traumatic and non-traumatic causes of AVN are known,including systemic autoimmune diseases. Among traumatic causes, physicaltrauma, decompression sickness or radiation may be cited. In the non-traumacases, two theories are disputed: the first concerns the occurrence of anintravascular coagulation and the second one attributes the ischemia toextravascular compression. AVN has been well described in patients withautoimmune diseases such as systemic lupus erythematosus, but in systemicsclerosis (SSc) patients, there have been limited case reports and case series. Wepresent a case of a 32-year old woman with systemic sclerosis on corticosteroid andavascular osteonecrosis and elaborating possible etiologies or mechanism ofavascular osteonecrosis in SSc.